Pengaruh Net Profit Margin, Return On Assets, Debt To Equity Ratio, Current Ratio Terhadap Harga Saham Pada PT. Jasa Marga Tbk. - Muhammad Syarif; Nurhayati Nurhayati (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The capital market is a means and infrastructure for companies or governments. The capital market is an activity in which a surplus of funds and demand for funds meet through negotiating securities for investment, namely stocks, bonds, mutual funds, derivatives (options and futures). Of all the capital markets above, the most well-known is the stock. Shares are a sign that a person or one of the parties (legal entity) participates in a company or limited liability company, including this capital, one party has the right to receive income, company assets and the right to attend shareholder meetings (Wijaya, 2017: 165).